Pengaruh Supply Chain Management (SCM) Terhadap Keunggulan Bersaing Perusahaan di Kota Medan - Ridho Fachrozie; Ahmad Muharmansyah Rezeki Maulana; Siti Aisyah (Universitas Muhammadiyah Enrekang, 2022)
The tighter the competition between companies, the more competitive advantage and increased performance are needed for companies to be able to survive in the business world, which is thought to be obtained through Supply Chain Management. This study aims to determine whether there is a significant influence between Supply Chain Management on company performance and competitive advantage. This research was conducted on companies in the city of Medan. The SCM variable is measured from several indicators, namely Strategic Supplier Partnership, Customer Relations, and Information Sharing. This study uses a qualitative approach using the literature study method. The results of this study prove that there is a significant relationship between Supply Chain Management on competitive advantage, Supply Chain Management on company performance, and competitive advantage on company performance in Medan City.